Production Cost Structure, Sales Growth, Inflation, and Profitability in Food and Beverage Companies - Jessie Veronika; Ari Agung Nugroho; Alim Bahri (Riset Akuntansi dan Bisnis Indonesia, 2026)
Purpose: This study examines the influence of audience segmentation and content innovation on TikTok marketing optimization among MSMEs in Pangkal Pinang City, Indonesia, addressing the limited empirical evidence in this regional digital marketing context. Methodology: A quantitative explanatory design was employed. Data were collected from 100 MSME owners and managers through Likert-scale questionnaires using purposive sampling methods. Validity, reliability, classical assumption tests, and multiple linear regressions were conducted using IBM SPSS Statistics 25. Results: Audience segmentation and content innovation both had significantly positive effects on TikTok marketing optimization. Together, they explained 81.3% of the variance, with content innovation emerging as the dominant predictor. Conclusions: Audience segmentation and content innovation are important factors in optimizing TikTok marketing among MSMEs, with creative content capabilities playing the strongest role in improving marketing performance. Limitations: This study was limited to one city, used only two predictors, and relied on cross-sectional self-report data, which may limit its generalizability and causal interpretation. Contribution: This study extends the social media marketing literature by applying the Resource-Based View, Uses and Gratification Theory, and STP framework in an MSME–TikTok context, while offering practical insights for small business digital marketing strategies.